GAGASAN KONSENTRASI PEMBIDANGAN PADA JURUSAN PENDIDIKAN AGAMA ISLAM DI FAKULTAS TARBIYAH PTAI - Ahmad Muthohar (IAIN Ponorogo, 2013)
Abstract: The idea of the program concentration was originated from public complaints of Madrasah users. They were less satisfied with the competence of the alumni who did not master the field of Islamic studies. Hence, Department of Islamic Education (PAI) ought to have strategic policies to establish new specific programs in accordance with the curriculum as a subject in schools and Madrasah. Unlike in public school that serves PAI as religious subject, Madrasah serves Al - Quran - Hadith, Aqidah Akhlaq, Fiqh and Islamic Cultural History. This should be responded by faculty to cope with the needs of Madrasah users by establishing the new programs such as: 1 ) Islamic Education ( PAI ), prepared to be a teacher of Islamic religion in schools, 2 ) Al - Qur’an-Hadith program, 3 ) Aqidah Akhlaq program, 4 ) Fiqh Program and ( 5 ) Cultural History of Islamic studies program, which are prepared to become the teachers in Madrasah. عنتقي ل .ةينيدلا سرادلا يجرل عمتلا ىواكش نع ةتان داولا فينصت ىلع زيكتلا ةركف نإ :صخلم ةيلك ف( ةيملسلا ةيبتلا مسق نإف اذل .ةيملسلا داولا ىلع نولوتسي ل نيذلا يجرلا ةءافكب ءلؤه .ةينيدلا سرادلاو )ةماع( سرادلا ف يساردلا جهنلا بسانت تلا ةديدلا ماسقلا حاتتفا هيلع ىغبني )ةيبتلا ةديقعلاو ،ثيدلاو نآرقلا ةدام ةينيدلا سرادلا فو ،ةيملسلا ةيبتلا ةدام )ةينيدلا يغ( سرادلا ف نوكت ةيبتلا مسق )1 : يه اديدج اهحاتتفا يغبني تلا ماسقلا نإف ،ةيملسلا ةفاقثلا خيراتو هقفلاو ،قلخلاو مسق )5 ،هقفلا مسق )4 ،قلخلاو ةديقعلا ةسارد مسق )3 ،ةيثيدلاو ةينارقلا ةساردلا مسق )2 ،ةيملسلا .ةينيدلا سرادلا ف يسردم لبقتسلا ف بلطلا نوكيل ،ةيملسلا ةفاقثلا خيرات